2004
DOI: 10.1530/eje.0.1510557
|View full text |Cite
|
Sign up to set email alerts
|

Low triiodothyronine (T3) state: a predictor of outcome in respiratory failure? Results of a clinical pilot study

Abstract: Background and aim: Various low triiodothyronine (T3) states have been described in severe nonthyroidal diseases and associated with a poor prognosis in cardiovascular disease patients. We assessed thyroid function in patients with severe respiratory failure from pulmonary disorders, and needing invasive or noninvasive mechanical ventilation, in order to evaluate the prognostic value of nonthyroidal illness syndrome. Methods: We studied 32 consecutive patients with acute or acute-on-chronic respiratory failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 13 publications
3
72
2
1
Order By: Relevance
“…1). The decreased T 3 and TSH and the increased rT 3 serum levels observed in this model of acute inflammatory lung injury are in agreement with those seen in the clinical setting of critical illness in patients with acute lung injury (ALI) and in animal models of acute illness (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Resultssupporting
confidence: 83%
“…1). The decreased T 3 and TSH and the increased rT 3 serum levels observed in this model of acute inflammatory lung injury are in agreement with those seen in the clinical setting of critical illness in patients with acute lung injury (ALI) and in animal models of acute illness (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Resultssupporting
confidence: 83%
“…This entity is characterized by a constant decrease in T 3 serum concentrations, and variable abnormalities of other thyroid hormone levels (4). It is secondary to severe acute (e.g., septic shock, myocardial infarction) (8,9) or chronic (e.g., cancer, advanced acquired immunodeficiency syndrome) (23)(24)(25) diseases and it has been demonstrated to be a predictor of increased mortality (6,18). As expected in our population of independently-living non-severely ill people, ESS was rare, occurring in only 3.4%.…”
Section: Discussionsupporting
confidence: 55%
“…In acute ESS, it was shown that the decrease in T 3 and the increase in rT 3 are related to mortality (5)(6)(7)(8)(9)(10). In nonacutely ill elderly, T 3 and rT 3 are often decreased and increased respectively, but many questions remain as to whether these disturbances are due solely to aging or to poor health status (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has indicated that low T 3 is associated with clinical outcomes in patients with various chronic diseases, including congestive heart failure, respiratory failure, and liver cirrhosis (13,14,15,16). Since low T 3 is the most common disturbance of thyroid hormone levels in ESRD patients, the adverse impact of low T 3 on patient survival has been widely explored in patients on maintenance hemodialysis (HD) and peritoneal dialysis (PD) (17,18).…”
Section: Introductionmentioning
confidence: 99%